Răspuns :
[(a+a: 5): 3-3]*13/6=13/2
[(a+a: 5): 3-3]*2, 1(6)=6, 5
(a+a: 5): 3-3=3
(a+a: 5): 3=6
a+a: 5=18
Inmultim cu 5
5a+a=90
6a=90
a=15
[(a+a: 5): 3-3]*2, 1(6)=6, 5
(a+a: 5): 3-3=3
(a+a: 5): 3=6
a+a: 5=18
Inmultim cu 5
5a+a=90
6a=90
a=15
Notam cu a numarul
1/3 ( a+a/5)= 1/3 x 6a/5 =2a/5
(2a/5 - 3) x13/6 = 13/2
2a/5 -3 = 13/2 x 6/13
2a/5 -3 = 3 se aduc la numitorul 5
2a-15=15
2a=30
a=15 numarul initial
1/3 ( a+a/5)= 1/3 x 6a/5 =2a/5
(2a/5 - 3) x13/6 = 13/2
2a/5 -3 = 13/2 x 6/13
2a/5 -3 = 3 se aduc la numitorul 5
2a-15=15
2a=30
a=15 numarul initial